The Procurement System for the Goods and Services Warship Repair - Authors I Made Subakti; Amin Setyo Leksono; Setyo Widagdo; I Made Jiwa Astika (Wacana: Jurnal Sosial dan Humaniora)
The Warship repair work requires timely completion and carries quite high risks. Considering the time to complete the work and the risks, a goods and services procurement system is needed that considers work safety factors and the readiness of warships. The work safety and procurement principles' specific requirements for warship repairs must be outlined in goods and services procurement documents, which can be used as a reference for selecting providers. The approach is a mixed method of questionnaires for the stakeholders involved in warship repairs. The data sources of the questionnaires are collected from units involved in the ship repairs, such as the implementing unit, the work supervision, the work feasibility assessors, and the service providers involved in the warship repairs. Processing research data uses the SEM method, then continues with SWOT analysis to obtain an ideal goods and services procurement system. The results of the analysis can provide suggestions for input into a system for procuring goods and services specifically for repairing warships to support national resilience in the maritime sector. The research was conducted at the Indonesian Navy Second Fleet Commands in Surabaya with the respondents of stakeholders involved in the warship repairs.